THE IMPACT OF IT GOVERNANCE PRACTICES ON PROFITABILITY: MEDIATING ROLE OF FINANCIAL TECHNOLOGY ADOPTION - Andi, Andi Nurlailiah Hamdiyani; Anis, Idrianita (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
Indonesia's economic recession in 2020 had an impact on the decrease in banking profitability. This situation encourages banks to formulate strategies that can increase profitability. IT governance can be a strategy for banks in minimizing the level of risk in using technology and determining the right technology investment for companies that can ultimately increase bank profitability. IT governance practices in this study use COBIT 2019. This study aims to empirically examine the effect of IT Governance practices on profitability through the mediating variable of technological innovation adoption. The population of this study is commercial banks listed on the IDX for the period 2017-2021. Sample selection using purposive sampling method, obtained a sample of 40 banks. The study used panel data estimation to test the direct effect using general least square and two stage least square for indirect effects. The results showed that IT governance practices had no direct effect on profitability. On the other hand, IT governance practices have a significant positive effect on the adoption of technological innovation. The results of indirect testing show that the adoption of technological innovation does not mediate the effect of IT governance practices on profitability. The results of this study provide practical implications for bank entities and policy recommendations related to the implementation of IT governance practices.